Environmental impacts and mitigation effectiveness of strategic perennialization - Englund, Oskar (Mid Sweden University, 2021)
Society faces the double challenge of increasing biomass production to meet the future demands for food,
materials and bioenergy, while addressing negative impacts of current (and future) land use. In the discourse,
land use change (LUC) has often been considered as negative, referring to impacts of deforestation and expansion of biomass plantations. However, strategic establishment of suitable perennial production systems in agricultural landscapes can mitigate environmental impacts of current crop production, while providing biomass for the bioeconomy.

Here, we explore the potential for such “beneficial LUC” in EU28. First, we map and quantify the
degree of accumulated soil organic carbon losses, soil loss by wind and water erosion, nitrogen emissions to
water, and recurring floods, in ∼81.000 individual landscapes in EU28. We then estimate the effectiveness in
mitigating these impacts through establishment of perennial plants, in each landscape.

The results indicate that there is a substantial potential for effective impact mitigation. Depending on criteria selection, 10–46% of the land used for annual crop production in EU28 is located in landscapes that could be considered priority areas for beneficial LUC. These areas are scattered all over Europe, but there are notable “hot-spots” where priority areas are concentrated, e.g., large parts of Denmark, western UK, The Po valley in Italy, and the Danube basin. While some policy developments support beneficial LUC, implementation could benefit from attempts to realize synergies between different Sustainable Development Goals, e.g., “Zero hunger”, “Clean water and sanitation”, “Affordable and Clean Energy”, “Climate Action”, and “Life on Land”.

I studien har vi utforskat potentialen för fördelaktig markanvändningsförändring genom strategisk perennialisering i Europa. Miljöproblematiken i fler än 81,000 individuella landskap har kvantifierats och potentialen att lindra miljöproblematik med hjälp av strategisk etablering av perenna grödor har uppskattats i varje enskilt landskap.

För mer information, se engelsk beskrivning.
Befintlig miljöproblematik och dess åtgärdspotential genom strategisk perennialisering - Environmental impacts and mitigation effectiveness of strategic perennialization
Beneficial land use change: Strategic expansion of new biomass plantations can reduce environmental impacts from EU agriculture
Keywords: Hydrography; Hydrografi; Land cover; Landtäcke; Land use; Markanvändning; Soil; Mark; Nitrogen emissions; Kväveläckage; Perennial crops; Perenna grödor; Soil carbon; Markkol; Erosion; Erosion; Flooding; Översvämningar; Environmental impacts; Miljöproblem; Biomass; Biomassa; Land use; Markanvändning; LUC; LUC; Ecosystem services; Ekosystemtjänster; Environmental Sciences; Miljövetenskap; Environmental Management; Miljöteknik och miljöledning; Bioenergy; Bioenergi; Agricultural Science; Jordbruksvetenskap; Environmental Sciences and Nature Conservation; Miljö- och naturvårdsvetenskap; Farming; Areella näringar; Environment; Miljö